The right to dividends – Can the associates still obtain them in case of the judicial dissolution of the company? - Stoican, Andreea (Technium Social Sciences Journal, 2020)
The issue of the distribution of the dividends, if refered only to what they represent, should not present uncertainties. Yet, the dividends, defined as a part of the profit of a company that belongs to each shareholder at the end of each fiscal year, in relation to the shares he owns, can raise new question under many aspects, not only regarding the moment from which they can be requested, or the person they belong to in case of transfer of shares (aspects to which the legal literature has already brought answers to), but also regarding their situation in case of dissolution of the company. As such, what we refer to in the current study is the possibility or not for the shareholders to exercise the right to dividends in case of a judicial dissolution of the company.